Correlation of Family Support and Quality of Life among DM type II Patients in Primary Healthcare - Rismayanti, Dewa Ayu; Nursalam, Nursalam; Widiarta, Gede Budi; Putra, G Nur Widya; Widiantari, Ni Putu; Ridayanti, Putu Windy; Suniyadewi, Ni Wayan (International Journal of Psychosocial Rehabilitation, 2020)
Diabetes mellitus is a chronic disease with rising epidemic prevalence in the world. In low middle-income countries like Indonesia, it causes major issues regarding morbidity and in the economic sector. As a new approach in diabetes management, there are two novel indicators that should be assessed. Quality of life is the main outcome besides blood glucose and family is involved as part of diabetes support. The aim of this study is to find out the correlation between those indicators. A cross-sectional study was done. 109 respondents who met the inclusion and exclusion criteria were selected. Inclusion criteria for the participants were adult type II DM patient, married and their spouse living together, recorded as regular patient in primary care for 2- 5 years. Hensarling Diabetes Family Support Scale (HDFSS) and DQOL Brief Clinical Inventory questioners were used to collect the data. The study was held at one in primary healthcare with a high incidence of DM in Buleleng. There were 109 respondents that were selected using purposive sampling methods and who completed the assessment. Data were analyzed using Spearman correlation with p-value = 0.0001. The result of the quality of life showed 50.5% was bad; 20.2% was moderate; and 29.4% was good. Using Spearman rank analysis p- value = 0,0001 and r = 0.318. Quality of life and family support among DM patients has a moderate correlation. Patients that often get support from family have a good quality of life. This powerful support will make people with type 2 DM always alert and be able to control their emotions against complications and can reduce feelings of inferiority to the condition of physical limitations experienced. Family support should be integrated in diabetes management in the primary care setting.